Characterization of Silver Nanoparticles Synthesized With Fungi Isolated From Cocoa and Orange Plantation Soils - Ogunsakin, OA; Ekundayo, EA; Ekundayo, FO; Olalemi, OA (Journal of Bio-Science, 2024)
Green synthesis of nanoparticles with various metals is being interested among researchers globally attention for due to their safety, environmental friendliness and non-toxicity in contrast to chemical synthesis. Here, fungi were isolated from rhizosphere of cocoa and orange obtained from Federal University of Technology, Akure using standard mycological techniques with the aim of synthesizing silver nanoparticles. The silver nanoparticles synthesized by these fungal isolates were characterized using Ultraviolet-Visible (UV-Vis) and Fourier Transmission Infra- Red (FTIR) spectroscopy. Seven fungi isolated from the soil samples viz. Nigrospora sphaerica, Penicillium discolor, P. digitatum, Neurospora crassa, Alternarium infectoria, Trichophyton verrucosum and Mucor mucedo. The colour transformation from yellow to brown indicated the formation of silver nanoparticles. All the isolates showed an intense peak in the wavelength range of 410-440 nm. The FTIR analysis of silver nanoparticles synthesized by N. sphaerica, P. discolor, P. digitatum, N. crassa, A. infectoria, T. verrucosum and M. mucedo revealed the existence of a band at different stretches of bonds at different peaks of 3314.36 cm-1, 3310.47 cm-1, 2412.22 cm-1, 3912.33 cm-1 3614.52 cm-1, 3852.11 cm-1 and 2112.11 cm-1, respectively. The silver nanoparticles synthesized could have the potential application in agricultural, pharmaceutical and food industries as well as petrochemical industries for the clean - up of crude oil contaminated soils. J. Bio-Sci. 32(2): 31-44, 2024